Smart Wearable for Detecting Dehydration - Mrs. N. Maragatham; B. Manoj Kumar; CH.V. Nihan Royal; J. Pavan Kumar; K. Venkatesh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Dehydration is a critical health concern affecting individuals across various demographics, from athletes to the elderly, often leading to severe complications like heatstroke, kidney damage, and chronic fatigue. Traditional hydration monitoring methods, such as manual tracking or periodic medical tests, fail to provide real-time insights, making them ineffective in preventing dehydration. This project proposes a smart wearable device that integrates multiple sensors—GSR, pH, DHT11, and PPG—to continuously monitor hydration levels with high accuracy. The collected data is processed using a Node MCU microcontroller and transmitted to a cloud-based platform, where machine learning algorithms analyze hydration patterns and issue real-time alerts. By leveraging advanced sensor technology and cloud analytics, this innovative solution ensures proactive hydration management, enhancing personal health monitoring and preventing dehydration-related risks.
Keywords: Internet of Things; Health; Sensors; Smart Wearable; Dehydration Detection; Hydration Monitoring; Electrodermal Activity (EDA); Heart Rate Variability (HRV); Skin Temperature Sensor; Real-time Monitoring; Non-invasive Sensors; Biometric Data Analysis; Sensor Accuracy; Machine Learning Integration; Wearable Technology; Healthcare Innovation; Sports Hydration Tracking; Environmental Interference; Wireless Charging; Mobile App Integration; User Comfort and Wearability